2019
DOI: 10.3390/ijerph16050713
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Dysmenorrhea on Quality of Life Among Spanish Female University Students

Abstract: (1) Background: Primary dysmenorrhea, which is characterized by menstrual pain in the absence of a pelvic pathology, is one of the main reasons for gynecological consultation. This study aimed to assess the prevalence of dysmenorrhea in a sample of university students, as well as their quality of life, and to examine the most common methods used for alleviating symptoms. (2) Methods: The participants comprised 305 female university students with a mean age of 20.32 ± 3.19 years who completed a self-report surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
103
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 44 publications
(55 reference statements)
7
103
0
9
Order By: Relevance
“…Hormonal contraceptives are the second choice of treatment for dysmenorrhea, and in our study, these were only taken by 11.71% of participants. Nonetheless, a reduced prevalence of dysmenorrhea and absenteeism was identified during menstruation in women who did take contraceptives, which is in line with the previous literature, however, this treatment is known to have possible adverse effects and is not accepted by all women [31,32].A number of authors consider the need to study the strategies used for treating menstrual pain and symptoms [5,22]. Although the management of menstruation is influneced by a diversity of contextual factors such as social, cultural, and economical factors, Armour et al highlight the urgent need on a global level to provide greater information on self-care regarding the management of menstruation, as, currently, most women worldwide fail to choose the best self-care option in this matter [31].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Hormonal contraceptives are the second choice of treatment for dysmenorrhea, and in our study, these were only taken by 11.71% of participants. Nonetheless, a reduced prevalence of dysmenorrhea and absenteeism was identified during menstruation in women who did take contraceptives, which is in line with the previous literature, however, this treatment is known to have possible adverse effects and is not accepted by all women [31,32].A number of authors consider the need to study the strategies used for treating menstrual pain and symptoms [5,22]. Although the management of menstruation is influneced by a diversity of contextual factors such as social, cultural, and economical factors, Armour et al highlight the urgent need on a global level to provide greater information on self-care regarding the management of menstruation, as, currently, most women worldwide fail to choose the best self-care option in this matter [31].…”
Section: Discussionsupporting
confidence: 78%
“…The high rates of absenteeism associated with dysmenorrhea and to an elevated intensity of menstrual pain could be related to an incorrect management of menstruation in Spain. As noted in former studies, most young women with dysmenorrhea do not consult a health professional, relying on self-medication [5,22]. Several authors have found that many young women with dysmenorrhea are able to endure menstrual pain and symptoms, understanding these as a typical aspect of a woman's life, normalizing their own menstrual experiences, even if these entail limitations [27][28][29].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…3,4 Primary dysmenorrhea is considered as one of the main problems in women and in public health so that WHO refers to it as the main cause of chronic pelvic pain. 5 In fact, in addition to its huge economic burden, 6 dysmenorrhea affects different dimensions of life and causes limitations in daily activities 7,8 and low sleep quality, 9,10 as well as negatively affect the patient's mood, lead to depression, stress and anxiety. 8,11,12 Although the main cause of primary dysmenorrhea is not well recognized, most studies show an increase in the levels of prostaglandins E2α (PGE2α), F2α (PGF2α), and leukotriene during menstruation and this, in turn, results in more uterine muscle contractions and cramps.…”
Section: Introductionmentioning
confidence: 99%
“…Essential oils can be absorbed via olfaction, through the external skin, internal skin, and ingestion and the applications are divided into inhalation, topical use, and oral use. Song et al [52], Lee et al [56] and Fernández-Martínez et al [3] reported that aromatherapy massage was an effective intervention for reducing dysmenorrhea [3,52,56]. Chinese herbal medicines (CHM) are well-accepted in the treatment of primary dysmenorrhea in East Asia, such as China, Korea, and Japan.…”
Section: Introductionmentioning
confidence: 99%